(untitled) (Bangladesh Medical Journal, 2019)
Adverse cutaneous drug reaction (ACDR) is a common issue in dermatology practice and it is crucial for every medical practitioner to remain updated of its pattern. It was a hospital based crosssectional observational study, conducted over 130 patients with adverse cutaneous drug reactionin the outpatient department of dermatology of Bangabandhu Sheikh Mujib Medical University (BSMMU). Majority of reaction was developed within one week of taking drug. Fixed drug eruption (FDE) was present in 18.5% cases followed by maculo-papular, Stevenson-Johnson-Syndrome-Toxic epidermal necrolysis (SJS- TEN), urticaria, urticaria + angioedema, lichenoid drug reaction, erythema multiforme, acneiform eruption, exfoliative dermatitis, pityriasiform, hyperpigmentation, acute generalized exanthematous pustulosis, drug induced hypersensitive syndrome, vasculitis, purpura, photosentivity, psoriasiform and other non-specific reactions. Anti convulsants (26.9%), NSAIDs (20.0%) and anti amtimicrobials (17.7%) are the most common drug group causing adverse cutaneous reaction. Many of the ACDR caused by anticonvulsants, NSAID and antimicrobials are even life threatening. Bangladesh Med J. 2018 Jan; 47 (3): 32-36